2006
DOI: 10.1007/11844297_68
|View full text |Cite
|
Sign up to set email alerts
|

Neuroevolution with Analog Genetic Encoding

Abstract: Abstract. The evolution of artificial neural networks (ANNs) is often used to tackle difficult control problems. There are different approaches to the encoding of neural networks in artificial genomes. Analog Genetic Encoding (AGE) is a new implicit method derived from the observation of biological genetic regulatory networks. This paper shows how AGE can be used to simultaneously evolve the topology and the weights of ANNs for complex control systems. AGE is applied to a standard benchmark problem and we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Some authors use binary or real encoding (representation of the networks in a binary or real number string) [37], [38], or indirect coding [39], [40], but G-Prop evolves the initial parameters of the network (initial weights and learning constants) using specific genetic operators. At the lowest level, an MLP is an object instantiated from the MLP C++ class.…”
Section: The Methodsmentioning
confidence: 99%
“…Some authors use binary or real encoding (representation of the networks in a binary or real number string) [37], [38], or indirect coding [39], [40], but G-Prop evolves the initial parameters of the network (initial weights and learning constants) using specific genetic operators. At the lowest level, an MLP is an object instantiated from the MLP C++ class.…”
Section: The Methodsmentioning
confidence: 99%
“…Other related task decomposition approaches in the literature include analog genetic encoding (AGE) [10,11,36,37]. Nevertheless, unlike RMGEP, AGE uses alphabetic labels or tokens which separate coding from non-coding parts of the genome to evolve parts of a system.…”
Section: Regulatory Multigenic Gene Expression Programmingmentioning
confidence: 99%
“…The initial population contained genomes of random length, , ranging from 2 to 20 genes, with indices chosen at random from [1,100], and values chosen at random from [−30, 30]. With this setup, no one genome contains all of the 100 available frequencies, but with very high probability all frequencies are present in the population.…”
Section: Setupmentioning
confidence: 99%
“…Indirect or generative encoding schemes for neural network phenotypes [1,5,6,9] offer the potential of allowing very large networks to be represented compactly. In previous work [7], we showed that encoding neural network weight matrices indirectly as a set of Fourier-type coefficients can reduce the search space dimensionality and help to discover more 'regular' networks which are simpler in the Kolmogorov sense (the program required to encode them is much shorter).…”
Section: Introductionmentioning
confidence: 99%